Experimental and computational study of the inclusion complexes of β-cyclodextrin with the chemical warfare agent soman (GD) and commonly used simulants. Issue 60 (2nd August 2017) - Sambrook, Mark R.; Vincent, Jack C.; Ede, Jayne A.; Gass, Ian A.; Cragg, Peter J.
Abstract : The inclusion complexation of the Chemical Warfare Agent soman (GD) by β-cyclodextrin is studied by both experimental and computational approaches. Abstract : The hydrophobically driven inclusion complexation of the Chemical Warfare Agent (CWA) pinacolyl methylphosphonofluoridate (soman, or GD) by β-cyclodextrin (β-CD) is studied both experimentally and computationally. Semiempirical modelling (PM6) adds further insight to the understanding of the CD–GD complex and the preferential binding of P(+) isomers over P(−). Comparison of the CD–GD complex to those formed by β-CD with commonly used trialkyl phosphate and dialkyl methylphosphonate simulants furnishes preliminary supramolecular agent–simulant correlation data. Such comparison studies will have utility in the design of new CWA-responsive materials.